High-energy synchrotron study of in-pile-irradiated U–Mo fuels. (15th March 2016) - Miao, Yinbin; Mo, Kun; Ye, Bei; Jamison, Laura; Mei, Zhi-Gang; Gan, Jian; Miller, Brandon; Madden, James; Park, Jun-Sang; Almer, Jonathan; Bhattacharya, Sumit; Kim, Yeon Soo; et al.
Abstract: Here synchrotron scattering analysis results on U–7wt.%Mo fuel specimens irradiated in the Advanced Test Reactor to three burnup levels (3.0, 5.2, and 6.3 × 10 21 fission/cm 3 ) are reported. Mature fission gas bubble superlattice was observed to form at intermediate burnup. The superlattice constant was determined to be 11.7 and 12.0 nm by wide-angle and small-angle scattering respectively. Grain sub-division takes place throughout the irradiation and causes the collapse of the superlattice at high burnup. The bubble superlattice expands the U–Mo lattice and acts as strong sink for radiation-induced defects. The evolution of dislocation loops was, therefore, suppressed until the bubble superlattice collapsed. Graphical abstract: